Application Challenges in Fiber and Textile Electronics. Issue 5 (5th July 2019) - Wang, Lie; Fu, Xuemei; He, Jiqing; Shi, Xiang; Chen, Taiqiang; Chen, Peining; Wang, Bingjie; Peng, Huisheng
Abstract: Modern electronic devices are moving toward miniaturization and integration with an emerging focus on wearable electronics. Due to their close contact with the human body, wearable electronics have new requirements including low weight, small size, and flexibility. Conventional 3D and 2D electronic devices fail to efficiently meet these requirements due to their rigidity and bulkiness. Hence, a new family of 1D fiber‐shaped electronic devices including energy‐harvesting devices, energy‐storage devices, light‐emitting devices, and sensing devices has risen to the challenge due to their small diameter, lightweight, flexibility, and weavability into soft textile electronics. The application challenges faced by fiber and textile electronics from single fiber‐shaped devices to continuously scalable fabrication, to encapsulation and testing, and to application mode exploration, are discussed. The evolutionary trends of fiber and textile electronics are then summarized. Finally, future directions required to boost their commercialization are highlighted. Abstract : The application challenges faced by fiber and textile electronics are discussed, from single fiber‐shaped devices, to continuously scalable fabrication, to encapsulation and testing, and to exploration of application modes. Evolutionary trends and new directions for future study are also provided.